Perlindungan hukum bagi konsumen dan pelaku usaha dalam jual beli akun Genshin Impact menggunakan jasa rekening bersama melalui media sosial - Ruba’i, Ahmad Ibnu (Maliki Interdisciplinary Journal, 2024)
This article discusses legal protection for consumers and business actors when buying and selling Genshin Impact accounts using joint account services via social media. The discussion includes legal protection that can be provided to consumers in terms of online game account buying and selling transactions, including consumer rights and obligations as well as resolving disputes that may arise. Apart from that, this article will also discuss legal protection for business actors who provide joint account services in buying and selling game accounts via social media, including legal responsibilities and relevant dispute resolution procedures. Through an analysis of applicable laws and regulations, this article aims to provide a deeper understanding of legal protection for both parties involved in buying and selling Genshin Impact accounts using joint account services via social media.